2019
DOI: 10.1155/2019/5168652
|View full text |Cite
|
Sign up to set email alerts
|

The Wound Healing Effect of Doxycycline after Corneal Alkali Burn in Rats

Abstract: Purpose To evaluate the wound healing effect of doxycycline and its underlying mechanisms in a rat model of corneal alkali burn. Methods Male SD rats were administered 1.0 N NaOH in the right cornea for 25 seconds and randomly divided into the doxycycline group and the control group, with 84 rats in each group. 1.0 g·L−1 doxycycline eye drops (doxycycline group) or vehicle (control group) was topically instilled onto the rat cornea after chemical injury. Three days, 7 days, and 14 days after alkali burn, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…endothelial [35]. In the alkali injury of the cornea, MMP-9 is responsible for the degradation of the basement membrane and tight junction between epithelial cells [16]. Our H&E staining showed that the existence of interrupted squamous epithelium was significant in the cornea injured with CEES; however, it was improved in the long run treatment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…endothelial [35]. In the alkali injury of the cornea, MMP-9 is responsible for the degradation of the basement membrane and tight junction between epithelial cells [16]. Our H&E staining showed that the existence of interrupted squamous epithelium was significant in the cornea injured with CEES; however, it was improved in the long run treatment.…”
Section: Discussionmentioning
confidence: 67%
“…Before beginning the study, all rats received 0.3% tobramycin eye drops to prevent corneal infection [16]. At the 0 day, rats belonging to the groups 2-5 were anesthetized by 35 mg/kg body weight, ketamine hydrochloride 10% and xylazine 2% combination (Alfasan Company, Woerden, The Netherlands) to painless the corneal analgesia.…”
Section: In Vivo Animal Model Of Corneal Sm Injurymentioning
confidence: 99%
“…23,24 Doxycycline has also been shown to speed up repair and healing of the cornea by decreasing matrix metalloproteinases (MMPs) which decrease levels of inflammatory cytokines. [25][26][27] Tarsorrhaphy (partially sewing the eyelids closed) is an effective method to keep the cornea hydrated and oxygenated.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TGF-ß results in more transparent cornea after corneal alkali burn 19 . Mice wounded by corneal alkali burn and given TGF-ß inhibitor also had less inflammatory cell infiltration and myofibroblasts than the control group and had more transparent corneas and less neovascular at day 20 observation 20 .…”
Section: Discussionmentioning
confidence: 99%